(untitled) (Prostor, 2022)
Open spaces in neighborhoods are children’s main living spaces, closely related to their daily activities. There is an increasing awareness that the physical form of the neighborhood plays a critical role in children’s activity, by offering opportunities for exploration and interaction. The aim of this paper is to explore the impact of the spatial configuration of buildings on children’s activity on the example of a residential area in the city of Oum El Bouaghi (Algeria) as the research object. The hypothesis of this work indicates that spatial configuration and the location of the buildings, in particular, the way in which the site is embedded are important variables in children’s outdoor activity. Based on this hypothesis, both quantitative and qualitative methods are used together through Space Syntax and Snapshot Observations. Findings indicate that the extent and character of children’s outdoor activities are greatly influenced by the physical characteristics of the neighborhood environment in residential areas through the degree of space enclosure interpreted by visibility and accessibility. By uncovering the impact of spatial configuration, this research offers an approach to designers for rethinking and considering new insights into managing and designing current and future spaces in light of children’s preferences and behavior patterns.